170 Recurrence of ovarian cancer with distant metastasis after five years: a single institute experience. (13th November 2020) - Chew, K; Nirmala, K; Mohamad Nasir, S
Abstract : Objective: Ovarian cancer is the commonest death of gynaecological cancer worldwide. To date, data from literature regarding recurrence with distant metastasis after 5 years is scarce. This study aim to identify the risk factors and outcome of recurrence ovarian cancer with distant metastasis. Methods: Form 861 medical record of patients with ovarian cancer reviewed, only one patient (0.11%) had recurrent ovarian cancer with distant metastasis to spleen. Results: A 51 years old lady with no co-morbid history had primary debuking surgery followed by adjuvant chemotherapy for high grade serous ovarian adenocarcinoma stage 3c. Her BRCA test result was negative. She was under surveillance follow-up with no evidence of recurrence from biochemical profile (CA-125) and imaging study until 7 years later. Her CA-125 level increased 2 fold from the baseline with solitary splenic recurrence of ovarian cancer from the CT scan. Fine needle biopsy of the splenic mass revealed metastatic serous adenocarcinoma. She underwent an uncomplicated splenectomy followed by 6 cycles of adjuvant chemotherapy. The histopathology report showed metastatic serous adenocarcinoma. After 2 years of the treatment, she is still under surveillance with no evidence of recurrence. Conclusion: Recurrence of ovarian cancer with distant metastasis is very rare. Cytoreduction surgery (splenectomy in the case described above) followed by adjuvant chemotherapy showed promising result to patient.